A revolution for our rights : indigenous struggles for land and justice in Bolivia, 1880-1952 - Gotkowitz, Laura (E-Duke books scholarly collection., 2007)
Analyzes struggles over citizenship and nationhood in Bolivia, following the fate of subaltern projects for political inclusion and asking why ethnic/racial claims were more effectively incorporated into the revolutionary agenda than were gender demands.